Restoration of the striatal circuitry: from developmental aspects toward clinical applications - Pauly, Marie-Christin; Piroth, Tobias; Döbrössy, Máté; Nikkhah, Guido (Frontiers in Cellular Neuroscience, 2012)
In the basal ganglia, the striatum is a highly complex structure coordinating motor and cognitive functions and it is severely affected in Huntington’s disease (HD) patients. Transplantation of fetal ganglionic eminence derived precursor cells aims to restore neural circuitry in the degenerated striatum of HD patients. Pre-clinical transplantation in genetic and lesion HD animal models has increased our knowledge of graft vs. host interactions, and clinical studies have been shown to successfully reduce motor and cognitive effects caused by the disease. Investigating the molecular mechanisms of striatal neurogenesis is a key research target, since novel strategies aim on generating striatal neurons by differentiating embryonic stem cells or by reprogramming somatic cells as alternative cell source for neural transplantation.